Depression among frontline medical and paramedical staff during the coronavirus pandemic - O. Maatouk; R. Kammoun; I. Kammoun; K. Souabni; M. Karoui; H. Nefzi; F. Ellouz (European Psychiatry, 2022)
Introduction The current coronavirus pandemic is a unique and unusual situation. It is putting the general population under severe strain. However, frontline medical and paramedical staff remain particularly vulnerable to depression because of its close contact with patients.